Women, Social Media, and Politics: Perspectives on Inequalities, Resistance, and Contested Narratives - López, Ricardo Enrique Grundy; Velazco, Renato Paredes; Paredes, Doris Cornejo; Quispe, Javier Lucho Valero; Revilla, Cintya Yadira Vera (Journal of Cultural Analysis and Social Change, 2025)
This essay critically explores the tension between structural inequality and women’s agency in digital politics through a comparative, intersectional framework. It is based on a qualitative review of academic and empirical studies published between 2015 and 2025, selected according to their relevance to gender, media, and political participation. The comparative focus includes case studies from Latin America, Asia, and Africa—regions chosen for their contrasting sociopolitical contexts and varying degrees of digital inclusion—aiming to capture both diversity and asymmetry in women’s online participation. The analysis maps six interconnected dimensions: gender gaps in access to and use of technology; symbolic violence and online hate speech; the clash between legacy media representations and digital narratives; young women’s activism on platforms such as Twitter (now “X”) and Facebook; satire as a political tool in authoritarian settings; and transnational women’s networks for global mobilization. The methodological approach combines a critical discourse analysis of secondary sources with a comparative synthesis across regions. Findings indicate that digital technologies, on their own, do not guarantee women’s political inclusion; instead, they frequently reproduce or deepen pre-existing exclusions—particularly where ethnicity, class, age, or geography intersect. Nonetheless, digital spaces open new avenues for participation, allowing women to create autonomous narratives and communities of solidarity. Digital feminist activism emerges in multiple forms, from contesting misogynistic discourse to deploying humor, art, and transnational advocacy. The central argument is that digital networks constitute ambivalent arenas where exclusion and empowerment coexist. Expanding women’s full digital citizenship requires inclusive technology policies, coordinated strategies against online violence, and stronger cross-border support networks.